Administering Homework Self-Grading for an Engineering Course. Issue 3 (3rd July 2022) - Chang, Kevin; de Lemos Coutinho, Lucas
Abstract: Homework problem sets allow a student to measure personal understanding and enable an instructor to evaluate individual student and overall class performance. For this study, students were asked to self-grade their homework assignments for a junior-level Fundamentals of Transportation Engineering course. Although self-grading studies have been previously performed, this technique has not been fully examined for an engineering course. The main objectives of this study were to evaluate homework self-grading performance and accuracy by engineering students and to describe how these self-grading aspects evolved during the semester as students became more familiar with this grading approach. The study concluded that while some students benefited from and embraced the opportunity to personally review their homework assignments, other students did not perceive the intended benefits of this process.